Alcohol and cognitive control: effects of acute intoxication on the performance in several response-inhibitory tasks - Ivanec, Dragutin; Rebić, Veseljka (2014)
The aim of the study was to investigate the impact of different alcohol concentration in blood on the three basic motor and attention-perceptual abilities. Participants (N=24, repeated measures design) were tested at four levels of blood alcohol concentration (BAC): placebo ; 0.3 ; 0.5 and 0.8 g/kg. In every BAC condition participants performed three different tasks: go/no-go reaction time task, test of perceptual speed and classical Stroop task. The results showed that the different levels of alcohol concentration have statistically significant and linear effect on go/no-go reaction time task, as well as on the score in the test of perceptual speed. Increasing concentration of alcohol decreased reaction time and performance on perceptual speed test. Performance on the Stroop task was also influenced by alcohol consumption, but this effect was quadratic, not linear. Interference was lower in the placebo and 0.8 g/kg BAC condition compared to the one at the moderate BAC levels (0.3 and 0.5 g/kg). In all three tasks, statistical size effects were moderate, but in terms of absolute differences in performance, effects were small.
Projekt MZOS